Works Councils - Sand or Grease in the Operation of German Firms? - Thorsten Schank; Claus Schnabel; Joachim Wagner (Institute for the Study of Labor (IZA), 2002)
Using a large panel data set we investigate whether works councils act as sand or grease in the operation of German firms. Stochastic production frontier analysis indicates that establishments with and without a works council do not exhibit significant differences in efficiency.
Keywords: J50; 330; works council; codetermination; production frontier analysis; Germany; Betriebsrat; Mitbestimmung; Technische Effizienz; Unternehmensentwicklung; Schätzung; Deutschland